2023
DOI: 10.1007/s11277-023-10434-z
|View full text |Cite
|
Sign up to set email alerts
|

E-FEERP: Enhanced Fuzzy Based Energy Efficient Routing Protocol for Wireless Sensor Network

Abstract: Wireless Sensor Network (WSN) comprises thousands of tiny sensor nodes used in various monitoring applications to sense environmental conditions. WSN collects and organizes the sensed data and transmits to the Base Station (BS). Due to the limited battery energy of sensor nodes, optimal data collection and transmission techniques are necessary for the prolonged working of the sensor network. The Particle Swarm Optimization (PSO) method is used in this paper to form the cluster in WSN and a Fuzzy based Energy E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Narayan et al [37] employs fuzzy logic to optimize routing decisions, considering energy efficiency. This protocol aims to extend the network's lifespan by intelligently routing data while minimizing energy consumption, improving the overall performance of wireless sensor networks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Narayan et al [37] employs fuzzy logic to optimize routing decisions, considering energy efficiency. This protocol aims to extend the network's lifespan by intelligently routing data while minimizing energy consumption, improving the overall performance of wireless sensor networks.…”
Section: Related Workmentioning
confidence: 99%
“…The data collected by the sensors can be related to various environmental parameters, such as temperature, humidity, light, or motion, and they are used for applications like environmental monitoring, surveillance, or industrial automation. The nodes in a WSN communicate wirelessly, forming a distributed network that enables real-time data collection and analysis for various applications [1][2] [3]. The ubiquitous deployment of WSNs in various fields, including environmental monitoring, healthcare, and industrial automation, has brought about significant challenges related to energy efficiency and network longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a research work [22] suggested that there is an immense need for efficient data transmission and collection methods in WSNs due to limited battery power in nodes. The authors propose a cluster formation technique using Particle Swarm Optimisation and a Fuzzy-based Energy Efficient Routing Protocol (E-FEERP) to transmit data optimally from cluster heads to the Base Station.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2023, ref. [20] the WSN is responsible for gathering and arranging sensed data before sending it to the base station (BS). As the battery power of sensor nodes is limited, it is crucial to employ effective techniques for data collection and transmission to ensure the extended operation of the sensor network.…”
Section: Related Workmentioning
confidence: 99%